1999
DOI: 10.1037/0022-006x.67.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life: Expanding the scope of clinical significance.

Abstract: Clinical researchers have turned their attention to quality of life assessment as a means of broadening the evaluation of treatment outcomes. This article examines conceptual and methodological issues related to the use of quality of life measures in mental health. These include the lack of a good operational definition of the construct, the use of subjective versus objective quality of life indicators, and the nature of the relationship between symptoms and quality of life judgments. Of special concern is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
193
1
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(205 citation statements)
references
References 81 publications
1
193
1
10
Order By: Relevance
“…Some authors defend the use of specific instruments in quality of life studies, arguing that these may help elucidate the characteristics related to specific health issues, while other authors state that such specific instruments are restricted to symptoms and to dysfunctions, contributing little to a better understanding of quality of life aspects 33 . Within a broader health model, a general quality of life instrument may be more fruitful in the perspective of creating knowledge for better health care for individuals and for the social group 34 .…”
Section: Tabela 1 -Escores Da Distribuição Do Whoqol-bref E Do Ohip-1mentioning
confidence: 99%
“…Some authors defend the use of specific instruments in quality of life studies, arguing that these may help elucidate the characteristics related to specific health issues, while other authors state that such specific instruments are restricted to symptoms and to dysfunctions, contributing little to a better understanding of quality of life aspects 33 . Within a broader health model, a general quality of life instrument may be more fruitful in the perspective of creating knowledge for better health care for individuals and for the social group 34 .…”
Section: Tabela 1 -Escores Da Distribuição Do Whoqol-bref E Do Ohip-1mentioning
confidence: 99%
“…Kuhn et al proposed that emotional numbing plays an important role in psychosocial functioning but found that other symptom clusters also had unique relationships with different aspects of functioning as well [40]. One possibility is the QOLI itself, which strongly reflects life satisfaction [22]. It is not difficult to imagine how numbing-i.e., being unable to have loving feelings or feeling less interest in formerly pleasurable activities-could have the most pervasive (and pernicious) effects on one's satisfaction with life.…”
Section: Domainmentioning
confidence: 99%
“…Definitions of quality of life vary and include some combination of objective elements (such as income), functioning, and subjective well-being [22]. However, Mendlowicz and Stein suggest that the general consensus is that a definition should capture the subjective experience of well-being and the multidimensional nature of the construct [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to several researchers (e.g. Gladis, Gosch, Dishuk, & Crits-Christoph, 1999), HRQoL reflects a functioning component of quality of life and directly affects subjective well-being. Clarifying the relationship between PTSD symptoms and HRQoL would provide valuable suggestions for improving quality of life among individuals experiencing traumatic events.…”
Section: Introductionmentioning
confidence: 99%